Analisis Penyebab Pernikahan Usia Dini Di Kecamatan Pleret Kabupaten Bantul - Muhammad Sulkhan Zainuri; Hartoyo Hartoyo; Muhajir Muhajir; M.N.K Al Amin; Andrie Irawan; Iin Sunny Atmaja (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2019)
Many rural residents are still married under the age specified in the Indonesian marriage law. There are many reasons why they are forced to do it in Pleret sub-district there is an increasing trend of people who marry at an early age. A qualitative case study research was then conducted to naturally describe the causes of the practice of underage marriage in the research location. The socio-juridical approach was carried out on the data that had been collected through observation, documentation and in-depth interviews with informants selected by purpossive sample. Most of them do early marriage because of economic and educational factors. The causes of intervention or the role of parents or cultural customs do not have as much influence as the first two factors. The age limit of marriage in the legislation has not been clearly and strictly understood for their own future interests so that it still provides opportunities for the practice of early marriage.